Airport traffic optimisation and airdrome analysis using mathematical modelling - Douae Zbakh; Marwane Benhadou; Abderrahmane Benkacem; Abdelouahid Lyhyaoui (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
An airport is considered to be a complex system, so managers nowadays are looking for verifiable solutions that could be tested and virtually simulated, in order to optimize safety, improve regularity, and reduce delays and risks of collision. To respond to this dilemma, many solutions were tested using safe simulation methods. The specific problem tackled in this paper refers to aerodrome capacity optimization, and specialy arcrafts mouvements. For this purpose, we introduce a mathematical model that was applied to Mohamed V Casablanca Airport, and the corresponding event actualization and graph was constructed taking into account uncertainty in flight schedules, aircraft types and their stand. Finally, the airdrome model was simulated using a special parameter in Arena tool.